1989
DOI: 10.1136/gut.30.5.675
|View full text |Cite
|
Sign up to set email alerts
|

Olsalazine or sulphasalazine in first attacks of ulcerative colitis? A double blind study.

Abstract: SUMMARY Olsalazine (2 g/day) and sulphasalazine (3 g/day) were compared in a double blind three centre trial in 37 patients presenting with first attack of distal colitis. Sigmoidoscopic appearances, rectal biopsies, and symptom and stool diary records were used to assess benefit and adverse effects. Both groups showed a similar decrease in stool frequency (p<0001). The proportion of unformed stools was also decreased, but to a lesser extent (p<005) in those taking olsalazine (78% v 55%; p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 20 publications
(1 reference statement)
0
42
0
Order By: Relevance
“…Thus, 20 trials were included in the analysis (Fig. 1) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Of these 20 studies, 19 obtained acceptable Jadad score of 3 or more [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 20 trials were included in the analysis (Fig. 1) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Of these 20 studies, 19 obtained acceptable Jadad score of 3 or more [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The summary RR for overall improvement in three trials that compared SSZ and olsalazine [32,34,40] Fig. 7).…”
Section: Efficacymentioning
confidence: 99%
“…11 Sulfasalazine, mesalamine, and olsalazine have been proven to be effective in active ulcerative colitis. [12][13][14] These agents often require up to 6 weeks to exert their maximal benefit. As with topical therapy, a full response includes cessation of all symptoms and signs (including bleeding) and a return to a normal appearance of the colonic mucosa on sigmoidoscopy.…”
Section: 10mentioning
confidence: 99%
“…68,83,105,126,131 When compared to sulphasalzine, all 3 studies showed non-inferiority of olsalazine. 66,117,130 There was one study that compared olsalazine 3 g/d to Eudragit-L mesalazine 3 g/d and found similar rates of endoscopic remission. 94 There was one last study that looked at dose response of olsalazine, with findings favoring the higher dose (3 g/d) versus 0.75 g/d and 1.5 g/d.…”
Section: Olsalazine-inductionmentioning
confidence: 99%